2022
DOI: 10.1021/acs.jpcc.1c10781
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt–Copper Nanoparticles on Three-Dimensional Substrate for Efficient Ammonia Synthesis via Electrocatalytic Nitrate Reduction

Abstract: Ammonia (NH 3 ) is a valuable chemical for fertilizer production and for use as an effective hydrogen carrier. Electrocatalytic nitrate reduction has recently received great attention as an alternative for NH 3 synthesis due to its kinetically favorable reaction. However, this promising strategy suffers from low Faradaic efficiency (FE) at large current density (>100 mA cm −2 ) and low nitrate concentrations because of the competing hydrogen evolution reaction. Herein, we report a catalyst consisting of earth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 40 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Within the United States, typical nitrate levels in agricultural groundwater range between 0.2 and 0.4 mM, and about 80% of agricultural wells have nitrate concentrations less than the MCL of 10 mg/L NO 3 -N (0.714 mM) set by EPA 4 . Unfortunately, electrocatalysis can run into a significant extent of side reactions (e.g., hydrogen evolution), particularly under such low nitrate concentrations 21 , which thus severely affecting the energy efficiency. Furthermore, the low ionic conductivity of dilute nitrate waste sources requires the integration of an additional separation step, to remove and concentrate the nitrate before efficient electroconversion can occur (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Within the United States, typical nitrate levels in agricultural groundwater range between 0.2 and 0.4 mM, and about 80% of agricultural wells have nitrate concentrations less than the MCL of 10 mg/L NO 3 -N (0.714 mM) set by EPA 4 . Unfortunately, electrocatalysis can run into a significant extent of side reactions (e.g., hydrogen evolution), particularly under such low nitrate concentrations 21 , which thus severely affecting the energy efficiency. Furthermore, the low ionic conductivity of dilute nitrate waste sources requires the integration of an additional separation step, to remove and concentrate the nitrate before efficient electroconversion can occur (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Cu(111) has higher FE % of ammonia at low working potential than Cu(200). , Since the first electron transfer of the adsorbed NO 3 – to NO 2 – was the rate-limiting step, the utilization of porous substrates increased the electrode adsorption capacity, therefore promoting NO 3 – reduction. The strategy of mixing two metals enables faster interfacial charge transfer. First, the surface metal in variable electronic states, such as Fe­(II)/Fe­(III), Cu(0)/Cu­(I), Co­(II)/Co­(III), Ce­(III)/Ce­(IV), could be the charge mediator for hydrogen and nitrate reduction. Second, the neighboring H promptly regenerated the catalytic centers, thus accelerating the reduction of oxygenated nitrogen .…”
Section: Resultsmentioning
confidence: 99%
“…A high NH 3 selectivity of 94.4% and FE of 79.6% were achieved when utilizing the designed CuNi@C as a catalyst for the NO 3 − RR. Jeon et al 96 designed cobalt–copper (Co 1− x Cu x ) nanoparticles supported on a three-dimensional substrate for efficient and selective NH 3 synthesis via an electrocatalytic NO 3 − reduction. Typically, the optimized Co 0.5 Cu 0.5 catalyst performed at a high NH 3 FE of over 95% at −0.03 V with an NH 3 partial current density of ∼176 mA cm −2 at 50 mM nitrate, which is 7.3- and 1.7-fold higher than those of the pure Co and Cu counterparts, respectively.…”
Section: Efficient No3−rr Electrocatalystsmentioning
confidence: 99%